HUMAN RESOURCES COMPETENCE IN STATE FINANCIAL MANAGEMENT: MALAY CULTURAL PERSPECTIVE - Bobby Briando; Mohd Na'eim Ajis; Iwan Triyuwono; Unti Ludigdo (Jurnal Akuntansi Multiparadigma)
Abstract – Kompetensi Sumber Daya Manusia Pengelola Keuangan Daerah: Perspektif Budaya Melayu